A critical review of sub-adult age estimation in biological anthropology: Do methods comply with published recommendations?. (July 2018) - Corron, Louise; Marchal, François; Condemi, Silvana; Adalian, Pascal
Highlights: A critical review of 269 sub-adult age estimation methods is proposed. Standardized criteria from published recommendations are used for evaluation. Methods with valid sampling and statistical protocols are highlighted. Users are warned about the caveats of misapplication and misinterpretation. Abstract: The diversity of approaches and the high number of publications on sub-adult age estimation is a testament to the relevance of this particular area of forensic anthropological research. However, a downside of this diversity is the many methodological, sampling and statistical discrepancies between publications, which can lead to difficulties in method definition, application and comparison. Several authors have published recommendations highlighting standardized methodological parameters that should be respected and clearly appear in the original publications for anthropological methods to be valid. This study aims to objectively evaluate a corpus of 269 publications on dental and skeletal postnatal sub-adult age estimation using these recommendations translated into descriptors. These descriptors cover five sampling and five statistical parameters that can be considered valid or invalid according to published methodological recommendations. Parameter and descriptor distributions are shown in frequency tables and graphs, illustrating the general invalidity of the sampling and/or statistical protocols. Provided our corpus of methods is an accurate representation of available publications, the extrapolation of these results leads to conclude that most sub-adult age estimates are at worst invalid, at best questionable, and almost certainly method-dependent. In view of this study, rigorous and standardized sampling and statistical approaches should be preferred when applying and building sub-adult age estimation methods.